ORZEKANIE O PODZIALE MAJĄTKU WSPÓLNEGO MAŁŻONKÓW W ŚWIETLE BADAŃ AKTOWYCH - Słyk, Jerzy; Godlewska, Dominika (Zeszyty Prawnicze, 2016)
RULINGS ON THE DIVISION OF MATRIMONIAL ASSETS IN THE LIGHT OF RESEARCH ON COURT RECORDS Summary The article discusses the division of matrimonial assets in Poland after the cessation of community property. The first part of the article presents the ways in which the division may be effected, both in non-procedural and in divorce proceedings. The latter is rarely used in practice, despite the benefits it brings the divorcing spouses and the opinion of the Polish Supreme Court on this matter. The second part of the article presents the results of the research carried out by Dominika Godlewska on this issue.